Changes of Intestinal Oxidative Stress, Inflammation, and Gene Expression in Neonatal Diarrhoea Kids - Cheng, Yan; Yang, Chao; Tan, ZhiLiang; He, ZhiXiong (Frontiers in Veterinary Science, 2021)
Diarrhea and disorders in young goats are serious threats to the animals’ health, influencing the profitability of the goat industry. There is a need to better understand the potential biomarkers that can reflect the mortality and morbidity in neonatal diarrhea goats. Ten pairs of twin kid goats from the same does (one healthy and the other diagnosed as diarrhea) with the same age under 14 days after birth were used in this study. Since gastrointestinal infection is probably the first ailment in neonatal goats, we aimed to investigate the changes in oxidative stress, inflammation, and gene expression in the gastrointestinal tract of neonatal diarrhea goats based on an epidemiological perspective. The results showed the activity of glutathione peroxidase (GSH-Px) was less (P < 0.05) in the jejunum in neonatal diarrhea goats compared with control goats. However, the malondialdehyde (MDA) activities in the jejunum and ileum were higher (P < 0.05) in neonatal diarrhea goats. There was no significant difference in the super-oxide dismutase (SOD) and catalase (CAT) activity observed between the two groups (P > 0.05). For the concentrations of intestinal interleukin-2 (IL2) and interleukin-6 (IL6), only the IL-2 in ileum of neonatal diarrhea goats was higher than that from healthy control goats. The transcriptomic analysis of the jejunum showed a total of 364 differential expression genes (DEGs) identified in neonatal diarrhea goats compared with control goats. The Kyoto Encyclopedia of Genes and Genomes (KEGG) functional enrichment analysis of up-regulated DEGs was mainly related to the ECMreceptor interaction and axon guidance, and the down-regulated DEGs mainly related to the Arachidonic acid metabolism, complement and coagulation cascades, and alpha-Linolenic acid metabolism. Real-time PCR results showed that the expression of most toll-like receptor-4-(TLR4) pathway-related genes and intestinal barrier function-related genes were similar in the two groups. These results suggest that neonatal diarrhea goats experienced a higher intestinal oxidative stress compared with control goats. Thus, it is possible that the antioxidant capacity of young ruminants acts as an indicator of health status and the measurements of oxidation stress may be useful as diagnostic biomarkers, reflecting the mortality and morbidity in neonatal diarrhea goats.